2023
DOI: 10.1186/s12903-022-02705-1
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 infection rates and mitigation strategies in orthodontic practices

Abstract: Background COVID-19 has impacted and increased risks for all populations, including orthodontic patients and providers. It also changes the practice management and infection control landscape in the practices. This study aimed to investigate the COVID-19 infection and vaccination status of orthodontic providers and mitigation approaches in orthodontic practices in the United States during 2021. Methods A validated 50-question research electronic da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…A recent survey study evaluated the impact of COVID-19 on orthodontic practice management and found that approximately 52% of orthodontic providers offered teledentistry in their practice after the pandemic. This suggests that Teleorthodontics is a promising solution and is likely here to stay [ 18 – 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey study evaluated the impact of COVID-19 on orthodontic practice management and found that approximately 52% of orthodontic providers offered teledentistry in their practice after the pandemic. This suggests that Teleorthodontics is a promising solution and is likely here to stay [ 18 – 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The respiratory system is attacked by the corona virus, also known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). COVID-19 is the name of the illness caused by this viral infection (Durbin et al, 2023). The corona virus can result in serious lung infections, moderate respiratory system damage, or even death.…”
Section: Introductionmentioning
confidence: 99%